LINGUOCULTURAL AND LINGUOPRAGMATIC FEATURES OF PROFESSIONAL FOREIGN LANGUAGE COMMUNICATION IN THE MEDICAL SPHERE IN THE CONDITIONS OF INTERNATIONAL ACADEMIC MOBILITY - Mukhamedjanova Sitorabegim Djamolitdinovna (Bright Mind Publishing, 2025)
In the context of intensifying globalization processes and growing international academic mobility, the problem of effective professional foreign language communication in the medical field is of particular importance. The article is devoted to the analysis of linguocultural and linguopragmatic features of professional communication in the medical field that arise in a cross-cultural environment. The need to develop professional foreign language communicative competence in medical students participating in academic exchange programs is substantiated.
Keywords: Professional foreign language communication, medical field, linguacultural features, linguapragmatic features, academic mobility, intercultural communication.